Rating detection by reviews using ML and NLP towards mobile phone recommendation - Sarker, Md Wafi; Al Nahian, Sheikh Sanzid; Khan, Anjumand Moshtari; Oraib, Abdullah; Islam, Sikder Mohidul (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.